Genomewide association study of Parkinson's disease clinical biomarkers in 12 longitudinal patients' cohorts. Issue 12 (10th September 2019) - Iwaki, Hirotaka; Blauwendraat, Cornelis; Leonard, Hampton L.; Kim, Jonggeol J.; Liu, Ganqiang; Maple‐Grødem, Jodi; Corvol, Jean‐Christophe; Pihlstrøm, Lasse; van Nimwegen, Marlies; Hutten, Samantha J.; Nguyen, Khanh‐Dung H.; Rick, Jacqueline; et al.
Abstract: Background: Several reports have identified different patterns of Parkinson's disease progression in individuals carrying missense variants in GBA or LRRK2 genes. The overall contribution of genetic factors to the severity and progression of Parkinson's disease, however, has not been well studied. Objectives: To test the association between genetic variants and the clinical features of Parkinson's disease on a genomewide scale. Methods: We accumulated individual data from 12 longitudinal cohorts in a total of 4093 patients with 22, 307 observations for a median of 3.81 years. Genomewide associations were evaluated for 25 cross‐sectional and longitudinal phenotypes. Specific variants of interest, including 90 recently identified disease‐risk variants, were also investigated post hoc for candidate associations with these phenotypes. Results: Two variants were genomewide significant. Rs382940(T>A), within the intron of SLC44A1, was associated with reaching Hoehn and Yahr stage 3 or higher faster (hazard ratio 2.04 [1.58–2.62]; P value = 3.46E‐8). Rs61863020(G>A), an intergenic variant and expression quantitative trait loci for α‐2A adrenergic receptor, was associated with a lower prevalence of insomnia at baseline (odds ratio 0.63 [0.52–0.75]; P value = 4.74E‐8). In the targeted analysis, we found 9 associations between known Parkinson's risk variants and more severe motor/cognitive symptoms. Also, we replicated previous reports of GBA coding variants (rs2230288: p.E365K; rs75548401: p.T408M) being associated with greater motor and cognitive decline over time, and an APOE E4 tagging variant (rs429358) being associated with greater cognitive deficits in patients. Conclusions: We identified novel genetic factors associated with heterogeneity of Parkinson's disease. The results can be used for validation or hypothesis tests regarding Parkinson's disease. © 2019 International Parkinson and Movement Disorder Society